2003
DOI: 10.1140/epjd/e2002-00232-x
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of small lead clusters

Abstract: We have located the global minimum for all lead clusters with up to 160 atoms using a glue potential to model the interatomic interactions. The lowest-energy structures are not face-centred cubic as suggested previously. Rather, for N < 40 the majority of structures are decahedral or hexagonal close-packed, and beyond this size the structures do not correspond to any of the structural forms commonly found in clusters. However, these latter clusters are not simply disordered. High symmetry, magic number cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
1
30
0
1
Order By: Relevance
“…The current results further highlight how many-body potentials can lead to the stabilization of unusual structural forms. 11,17,21,38,47 Of course, at sufficiently large sizes the bulk structure, in this case hexagonal close-packed, should become most stable, but the energy differences found in this study suggest that the current clusters are far from this limit.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The current results further highlight how many-body potentials can lead to the stabilization of unusual structural forms. 11,17,21,38,47 Of course, at sufficiently large sizes the bulk structure, in this case hexagonal close-packed, should become most stable, but the energy differences found in this study suggest that the current clusters are far from this limit.…”
Section: Discussionmentioning
confidence: 68%
“…This paper should be seen in the context of a growing research program that has sought to understand how the observed structures for metal clusters depend on the form of the many-body potential. 11,17,38,46,47 Even for simple potentials of the embedded-atom (or glue) form (Eq. 2) this leads to significant complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 See Raoult et al (1989b), Cleveland and Landman (1991), Uppenbrink and Wales (1992), Turner et al (2000), , Baletto et al (2002b), Doye and Hendy (2003) and Section III.E for details on some specific systems.…”
Section: Energetics Of Free Nanoclustersmentioning
confidence: 99%
“…Число способов организации дисклинаций в по-литетраэдрических упаковках или введения дис-клинаций в многогранник {3,3,5} огромно [28]. Сле-довательно, большая конфигурационная энтропия жидкости связана с множеством всех политетраэ-дрических состояний.…”
Section: обсуждение результатовunclassified